Implementasi Strategi Promotion Mix Dalam Meningkatkan Jumlah Peserta Didik - Widyaningsih, Bekti; Rahmatika, Arivatu Ni'mati; Asparinza, Erif Fiantini Aulia (JoEMS (Journal of Education and Management Studies), 2024)
Paud Al-Amaanah is an early childhood education institution, located in Sambong Dukuh Jombang. The KB activities carried out can hone children's intelligence, instill character according to the child's age, and behave morally towards fellow friends and parents. This institution requires promotion to increase the number of new students. Therefore, this study aims to promote the strategies implemented so that the number of students increases. This study uses a qualitative descriptive approach by conducting field research. The results of this study are the elements of the 4 promotional strategies used, namely: advertising, personal selling, sales promotion, public relations can increase the number of students. The positive and negative impacts experienced when implementing the 4 element strategy at Paud Al-Amaanah Sambong Dukuh Jombang are seen and felt. The obstacles faced in implementing this strategy have also been experienced.